Successful Treatment of Refractory Synovitis, Acne, Pustulosis, Hyperostosis, and Osteitis (SAPHO) Syndrome with Baricitinib, a Janus Kinase Inhibitor - Yang J; Yuan C; Zhou S; Teng Z; Li M (Dove Medical Press, 2024)
Jianqiu Yang,1,2 Chunyu Yuan,1 Shengru Zhou,1 Zhicheng Teng,2 Min Li1 1Department of Dermatology, Dushu Lake Hospital Affiliated to Soochow University (Medical Center of Soochow University), Suzhou, People's Republic of China; 2Suzhou Medical College of Soochow University, Suzhou, People's Republic of ChinaCorrespondence: Min Li, Department of Dermatology, Dushu Lake Hospital Affiliated to Soochow University (Medical Center of Soochow University), No. 9, Chongwen Road, Suzhou, 215100, People's Republic of China, Tel +86-18936140383, Email lm@suda.edu.cnAbstract: Synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome, a rare immune-mediated inflammatory disease, poses diagnostic and therapeutic challenges owing to its multi-system involvement, high heterogeneity, and lack of specific laboratory tests. Additionally, lacking evidence-based treatment recommendations, with the primary approach focusing on symptomatic relief. Herein, we report the case of a 32-year-old Chinese woman who presented with recurrent, generalized multiple osteoarticular pain lasting over one year and skin erythema pustulosis for 11 months. Traditional treatments, including non-steroidal anti-inflammatory drugs (NSAIDs), corticosteroids, disease-modifying antirheumatic drugs (DMARDs), and other traditional approaches, yielded no significant effects. Despite the prior use of adalimumab and acitretin capsules, the treatment remained unsatisfying, especially regarding the skin lesions. Considering the complex pathogenesis of SAPHO syndrome, the patient was orally administered baricitinib (2 mg), a Janus kinase (JAK) inhibitor, twice daily. A notable improvement in both skin lesions and osteoarticular pain was observed within two weeks of treatment initiation. Subsequently, the dosage of baricitinib was halved and continued for an additional three months, during which regular follow-ups revealed neither disease recurrence nor adverse effects. Collectively, the successful treatment of refractory SAPHO syndrome with baricitinib presents a promising implication for addressing the therapeutic challenges of this rare autoimmune condition, offering a potential breakthrough in managing its complex manifestations.Keywords: SAPHO syndrome, autoinflammatory conditions, therapeutic challenges, baricitinib